The role of automatic stabilizers and emergency tax-benefit policies during the COVID-19 pandemic in Ecuador - H. Xavier Jara; Lourdes Montesdeoca; Iva Tasseva (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper makes use of tax-benefit microsimulation techniques to quantify the distributional effects of COVID-19 in Ecuador and the role of tax-benefit policies in mitigating the immediate impact of the economic shocks. Our results show a dramatic increase in income poverty and inequality between December 2019 and June 2020. The poverty rate, measured with the national poverty line, goes up from 25.7 to 58.2 per cent over this period and extreme poverty increases from 9.2 to 38.6 per cent. Inequality measured by the Gini coefficient increases substantially from 0.461 to 0.592. On average, household disposable income drops by 41 per cent. The new Family Protection Grant provides income protection for the poorest income decile. However, overall tax-benefit policies do little to mitigate the losses in household incomes due to the pandemic.
Keywords: D31; E24; H24; 330; COVID-19; microsimulation; poverty; inequality; Ecuador